Baray ho kar - Kashifa, Samad (book group Karachi, 2022)
Baray Ho Kar (When You Grow Up) is a common phrase used in Urdu to encourage children to dream big and set goals for their future. It's often used to inspire children to study hard, work diligently, and pursue their passions.